PELAKSANAAN PROGRAM PENGEMBANGAN PENDIDIKAN ANAK BERKEBUTUHAN KHUSUS DI SEKOLAH LUAR BIASA YAYASAN PENDIDIKAN NASIONAL (YAPENAS) DEPOK KABUPATEN SLEMAN TAHUN AJARAN 2012/2013 (JURNAL ILMIAH TUT WURI HANDAYANI, 2014)
The research is purposed to understand the implementation of education development program for disable students of Yapenas Depok Sleman who have students with different types of disability which of course in the implementation of development programs, there are in contrast to regular school.This study used a qualitative approach. The sources of data are derived from sources or informants which include head of school, vice-head of school, teachers, staff, parents, school committees, as well as documents relating to the implementation of education development program. The data collection techniques use observation, interviews, and document scrutiny. For the validity test of data, it is done by extending research, triangulation of data, and auditing or verification of data. The results show that (1) Disable School of National Education Foundation (Yapenas) in the implementation of development programs of education for disable students has involved all the components and the learning method which vary are guided by the teaching staff which meets the standards qualification of BSc and MSc degrees, so that in the implementation of education development programs for disable students, it is to be effective, namely targeted at students through skill and efficient, namely the skill activities which are developed and really produced to be having value selling which the value is greater than the required capital. Thus in accordance with the expectations target, it is proved that the graduates of disable school for disable students, Yapenas, have many independent, namely capable to build entrepreneurship itself such as developing fisheriesat home, able to make high value bags, able to manage a grocery store at home, so that its output accomplished the planned purposes. (2) The supporting factors of the implementation of education development programs for disable students are for accepting new students it can be served at any time in hours of service, availability of teachers who meet the qualifications, availability of varied instructional media and produce work skills which have high sales value, building of co-operation with business and/or industrial worlds. (3) The inhibiting factors in this program are the lack of teacher skills, delays in government funding, lack of administrative personnel, special tools and operators.